PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA KARYAWAN BAGIAN PRODUKSI PT BANDENG JUWANA) - Muhammad Adi Nugroho; Saryadi Saryadi; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2016)
Human resource management is currently looking at an employee in the company as a corporate asset. Although employees are viewed as assets of the company, the employee can not be obtained as easily as other company assets in the form of goods. This is because it takes also a match between the qualifications that companies want to qualifications held by the job applicant. This match is required by the company, so employees who work to help the company to achieve its vision and mission. The vision and mission of a company, will be obtained with the employee's performance. Leadership and working environment has an influence on employee performance through motivation as an intervening variable in the production employees of PT. Bandeng Juwana. Production employee performance can be seen from the achievement of production targets, but it has not succeeded in the production target is reached.In this study used a sampling technique is simple random sampling of 77 production employees of PT. Bandeng Juwana. The technique of collecting data using questionnaires and interviews, the research instrument was a questionnaire. The data obtained were analyzed qualitatively and quantitatively through validity and reliability test. While data analysis is done through a simple linear regression analysis, multiple linear regression, t-test, F test and path analysis.Based on the results of the analysis are known pathways that influence leadership variable and variable work environment for employee performance variables, namely, leadership variables have a direct effect of 0.332, and the work environment has a direct influence amounted to 0,348. Motivation as an intervening variable has an effect of 0.350 on the variable employee performance. Then if leadership through motivation to affect performance, it is known the effect of 0.486. Meanwhile, if the work environment through motivation to affect performance, it is known the effect of 0.949. Based on this it can be seen that, the influence of leadership and work environment on employee performance will be greater if through motivation. Based on the test results of variable F leadership, work environment and motivation on the performance together look that F count> F table (52.851> 2.73), and based on the results of multiple regression results also show that leadership, work environment and motivation to have a positive influence the performance of employees.The conclusion from this study is that there is a positive and significant influence between leadership and work environment on employee performance, through motivation as an intervening variable. The advice given is to be increased attention on variable motivation for increasing employee performance.